An EOQ Model for Quadratic Demand Rate, Parabolic Deterioration, Time Dependent Holding Cost with Partial Backlogging - N. K. Sahoo; P. K. Tripathy (International Journal of Mathematics And its Applications, 2018)
An economic order quantity model has been developed for deteriorating items with demand rate as a quadratic function of time. In the model, deterioration rate and holding cost are time dependent. The inventory shortage is discussed and partially backlogged. The backlogging rate is dependent on the waiting time for the next replenishment. Results are illustrated with numerical example along with sensitivity analysis for the model with respect to various parameters is carried out.